ARTIFICIAL INTELLIGENCE TOOLS IN WRITING CLASS: STUDENTS’ PREFERENCES AND LECTURERS’ PERCEPTIONS - Irma Suryani; Rahma Fithriani (ELTIN Journal, 2024)
One of the benefits of artificial intelligence in the field of education is that it aids in writing. The aims of this research are to explore University students’ preferences in using AI for writing and investigate lecturers' perceptions regarding the use of artificial intelligence tools in EFL writing class. Qualitative research methods with case study design employed in this study. The data was collected by using questionnaires and interview. Ten EFL students and three lecturers from three different universities in Indonesia were involved as the respondents of this research. The findings revealed that there are nine types of AI ​​tools used by students in writing classes such as Quillbot, Grammerly, Chat GPT, Humata AI, Resume AI, Jenni AI, Perplexity, Deepl, and AI writing. Apart from that, the data also revealed the views of the lecturers on the use of AI. The data showed that AI writing tool have the influences on students' writing that the use of AI has received positive responses. Therefore, it can be inferred that Artificial Intelligence tools can be used in writing classes as long as it does not violate code in writing and not dependency.